2013
DOI: 10.1016/j.mib.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Virus discovery and recent insights into virus diversity in arthropods

Abstract: Recent studies on virus discovery have focused mainly on mammalian and avian viruses. Arbovirology with its long tradition of ecologically oriented investigation is now catching up, with important novel insights into the diversity of arthropod-associated viruses. Recent discoveries include taxonomically outlying viruses within the families Flaviviridae, Togaviridae, and Bunyaviridae, and even novel virus families within the order Nidovirales. However, the current focusing of studies on blood-feeding arthropods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 56 publications
2
81
0
Order By: Relevance
“…It is striking that even our limited sampling in arthropods could yield such distinctive and phylogenetically diverse viruses. In contrast, lower levels of virus diversity are found in vertebrates, despite the previous studies of pathogen discovery in these species (34). In addition, since the vertebrate viruses tend to form paraphyletic groups in the phylogenetic trees (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…It is striking that even our limited sampling in arthropods could yield such distinctive and phylogenetically diverse viruses. In contrast, lower levels of virus diversity are found in vertebrates, despite the previous studies of pathogen discovery in these species (34). In addition, since the vertebrate viruses tend to form paraphyletic groups in the phylogenetic trees (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…The recent advent of high-throughput sequencing, such as RNASeq, has accelerated the identification of virus sequence discovery in organisms including arthropods (Chiu, 2013;Junglen & Drosten, 2013;Li et al, 2015;Lipkin & Firth, 2013;Liu et al, 2015). Here we report the identification of a novel virus from M. euphorbiae by sequencing and assembly of the aphid transcriptome.…”
Section: Introductionmentioning
confidence: 88%
“…It has been suggested that most of these newly discovered viruses share features that distinguish them from "classic" human pathogens, including (i) the inability to infect vertebrates or vertebrate cell lines, (ii) high prevalence, (iii) prolonged host infection, and (iv) vertical transmission (1,2,23). Based on these features, these mosquito viruses have been referred to as "commensal" microbes (3).…”
mentioning
confidence: 99%